Developing Muslim Entrepreneurs Through Socialization of Sharia-Based Entrepreneurship - Nur Syamsu; Dewi Salmita; Rachmawati A. Rifai; Moh. Anwar Zainuddin; Akzal , Akzal Ilham; Nurhanifa, Nurhanifa (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Datokarama Palu, 2024)
This community service aims to build student competencies in facing the challenges of digital transformation and human resource development (HR) in the technological era. This activity is carried out through socialization and training that aims to increase students' understanding of the importance of digital literacy, technology skills, and the development of soft skills needed in the modern world of work. The methods used include counseling, interactive discussions, and hands-on practice on various aspects of digital transformation, such as the use of digital platforms, data management, and character and competency development relevant to current industry needs. The results of this activity show that the socialization and training provided can increase students' knowledge and awareness of digital transformation and the importance of developing adaptive and innovative human resources. Thus, this activity is expected to help students prepare to compete in the technological era and become a competent workforce ready to face change.